2019
DOI: 10.1002/anie.201907832
|View full text |Cite
|
Sign up to set email alerts
|

Ice as Solid Electrolyte To Conduct Various Kinds of Ions

Abstract: Water, considered as a universal solvent to dissolve salts, has been extensively studied as liquid electrolyte in electrochemical devices. The water/ice phase transition at around 0 °C presents a common phenomenon in nature, however, the chemical and electrochemical behaviors of ice have rarely been studied. Herein, we discovered that the ice phase provides efficient ionic transport channels and therefore can be applied as generalized solid‐state ionic conductor. Solid state ionic conducting ices (ICIs) of Li+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…Previous researches have proven that pure ice cannot conduct current. [ 25 ] And we also cannot measure the ionic conductivities of pure ice and Zn(CH 3 COO) 2 salt, respectively, due to their very large resistances. Therefore, the two separated phases cause the frozen Zn(CH 3 COO) 2 solution to exhibit a very large resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researches have proven that pure ice cannot conduct current. [ 25 ] And we also cannot measure the ionic conductivities of pure ice and Zn(CH 3 COO) 2 salt, respectively, due to their very large resistances. Therefore, the two separated phases cause the frozen Zn(CH 3 COO) 2 solution to exhibit a very large resistance.…”
Section: Resultsmentioning
confidence: 99%
“…systematically measured the ionic conductivities of various salty ices prepared by freezing common inorganic salt aqueous solutions, and they found that these salty ices exhibited a certain ionic conductivities of ≈10 −7 –10 −4 S cm −1 at the temperature range of −20 to −5 °C, which makes it possible to use salty ices as electrolytes for EES devices. [ 25 ] If the salty ices can make the aqueous EES devices obtain superior electrochemical performance, it would be not necessary to consider the freeze problem of the aqueous electrolytes, thereby solving the drawbacks of low‐temperature electrolytes at the current stage. Unfortunately, the ionic conductivities of these reported salty ices still cannot meet the normal operation requirements of EES devices at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…which suffers from safety hazards such as leakage and combustion. [1,2,[20][21][22][23] Nevertheless, the large-scale application of SPEs in LMBs is still inevitably hindered because of the sluggish transport of Li ions and poor affinity of the Li/electrolyte interface. [24][25][26][27][28] Considering the ultrahigh reducibility of Li, serious parasitic reactions (e.g., Li reacts with poly(ethylene oxide) (PEO) to form Li 2 O, C 2 H 4 , and H 2 ) inevitably occur at the Li/PEO interface to harm the performances of batteries.…”
Section: Doi: 101002/adma202000223mentioning
confidence: 99%
“…However, the aqueous electrolyte owns narrow liquid-state temperature range. When temperature substantially decreases, common aqueous electrolyte easily gets frozen due to the high freezing point of water, which limits the mobility of ions and the wettability of electrolyte toward electrode 13 , resulting in deteriorative electrode-electrolyte interphase. However, there are abundant renewable natural resources in severely cold regions, and most of energy storage devices cannot endure low temperature 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%